Ground water quality analysis in faculty of agriculture and forest resource’s campus to produce Doksiew drinking water - VANNAPHON1, Anousith; CHANTHAKHOUN, Vonpasith; SINGPA, Bounlam; PHETLAMPHAN, Bounxian; MANYTHONG, Hor; TAYYAMATH, Khambou (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The analysis of ground water quality in Faculty of Agriculture and Forest Resources (FAF) campus, Souphanouvong University (SU) the aim of this study is to analyze water quality, detect contaminants of water and compare with the standard values ​​to be primary information in drinking water production for teachers and students in SU. Water quality needs to analyze: 1. Physical quality: Color, Taste, Odor, Turbidity. 2. Chemical quality: alkalinity (pH), Total Solids, Electric charge (EC) and Sodium chloride. 3. Biological quality: Total living cell counts (Total plate count) of the bacterium (Total coliform bacteria); (Escherichia coli) or (E. coli). Ground water sample was carried from filed to lab and analysis by water quality checker and interview with consumers, as well as students and teachers in SU for satisfaction after drinking water. This research result found that the value of pH, EC, Color, Turbidity, Total plate count are 8.1, 1.23 MS/cm, 2.3, 28 NTU, 270 CFU/ml, respectively. However, Coliform and E. coli bacteria are not detected. FAF’s ground water quality is under safety standard values certified by WHO, without the contaminants and accepted by consumers